PENERAPAN MOTODE PEMBELAJARAN KOOPERATIF MODEL JIGSAW DAPAT MENINGKATKAN HASIL BELAJAR IPA - Sakri Sakri (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2016)
Jigsaw learning model application research in improving learning outcomes IPA do students of class VI SDN Gintungan I district. Kembangbahu Kab. Lamongan School Year 2014/2015, with the aim that students can improve their learning outcomes. This study uses action research (action research) as much as two rounds. Each round consists of four phases: design, activities and observations, reflections, and refisi. Goal of this research is the students of class VI SDN Gintungan I district. Kembangbahu Kab. Lamongan. The data obtained as the result of formative tests, observation sheet teaching and learning activities. From the analysis it was found that student achievement has increased from cycle I to cycle II ie, Cycle 1 (71.00%), the second cycle (86.00%). The conclusion of the study is the Implementation Method in Cooperative Learning Jigsaw Model to Improve Learning Outcomes IPA positive effect on students' motivation. So that this model can be used as an alternative learning at school.